2020
DOI: 10.3390/cells9020485
|View full text |Cite|
|
Sign up to set email alerts
|

WNK2 Inhibits Autophagic Flux in Human Glioblastoma Cell Line

Abstract: Autophagy is a cell-survival pathway with dual role in tumorigenesis, promoting either tumor survival or tumor death. WNK2 gene, a member of the WNK (with no lysine (K)) subfamily, acts as a tumor suppressor gene in gliomas, regulating cell migration and invasion; however, its role in autophagy process is poorly explored. The WNK2-methylated human glioblastoma cell line A172 WT (wild type) was compared to transfected clones A172 EV (empty vector), and A172 WNK2 (WNK2 overexpression) for the evaluation of autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Our results agree with previous results in hepatocellular carcinoma WNK2- silenced cells, in which re-expression of WNK2-WT suppressed colony formation, whereas introducing mutated WNK2 increased colony formation capacity 43. In addition, upregulation of WNK2 expression has also been linked to apoptosis, senescence and autophagy in colon cancer and glioma cells, which are processes focused on cell cycle control 46 47…”
Section: Discussionsupporting
confidence: 92%
“…Our results agree with previous results in hepatocellular carcinoma WNK2- silenced cells, in which re-expression of WNK2-WT suppressed colony formation, whereas introducing mutated WNK2 increased colony formation capacity 43. In addition, upregulation of WNK2 expression has also been linked to apoptosis, senescence and autophagy in colon cancer and glioma cells, which are processes focused on cell cycle control 46 47…”
Section: Discussionsupporting
confidence: 92%
“…Alves et al [19] demonstrated that the WNK2 gene, a known glioma suppressor gene, negatively regulates the migration and invasion of glioblastoma cells and inhibits their autophagic flux.…”
mentioning
confidence: 99%